2013
DOI: 10.1093/scan/nst120
|View full text |Cite
|
Sign up to set email alerts
|

The heart-break of social rejection versus the brain wave of social acceptance

Abstract: The effect of social rejection on cardiac and brain responses was examined in a study in which participants had to decide on the basis of pictures of virtual peers whether these peers would like them or not. Physiological and behavioral responses to expected and unexpected acceptance and rejection were compared. It was found that participants expected that about 50% of the virtual judges gave them a positive judgment. Cardiac deceleration was strongest for unexpected social rejection. In contrast, the brain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
75
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 23 publications
16
75
3
Order By: Relevance
“…A bias score was calculated to examine whether participants anticipated significantly more acceptance than rejection feedback (Van der Veen et al, 2013). This bias score was derived from dividing the number of acceptance judgments by the number of total judgments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A bias score was calculated to examine whether participants anticipated significantly more acceptance than rejection feedback (Van der Veen et al, 2013). This bias score was derived from dividing the number of acceptance judgments by the number of total judgments.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, Van der Veen et al (2013) investigated feedback ERPs using the social judgment paradigm. Results of this study corroborated the enhanced brain activity after receiving social acceptance feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a great deal of research examining the RewP in response to monetary rewards, only a few other studies to date have examined the RewP/FN in response to social reward and/or rejection (Crowley, Wu, Molfese, & Mayes, 2010;Kujawa, Arfer, Klein, & Proudfit, 2014;Sun & Yu, 2014;van der Veen, van der Molen, Sahibdin, & Franken, 2013). These studies have demonstrated that social feedback elicits ERP responses that are similar, though not identical in timing or morphology in every study, to those previously observed in response to monetary reinforcement.…”
Section: Introductionmentioning
confidence: 91%
“…In studies that have included both acceptance and rejection feedback, the results have been more mixed. For instance, Sun and Yu (2014) observed both a negative deflection in the ERP waveform in response to negative social feedback and a positive-going deflection in response to positive social feedback, while van der Veen and colleagues (2013) only observed a positive deflection in the ERP waveform in response to expected acceptance feedback. Kujawa, Arfer, and colleagues (2014), however, observed a negative-going deflection that was enhanced for rejection and reduced for acceptance feedback.…”
mentioning
confidence: 96%
“…Thereby, effects of social evaluation (acceptance vs. rejection) and expectancy (expected vs. unexpected outcomes) were manipulated. Early feedback evaluation (FRN component) was mostly sensitive to expectancy violations (Dekkers, Van Der Molen, Gunther Moor, Van Der Veen, & Van Der Molen, 2015; Van Der Molen, Dekkers, Westenberg, Van Der Veen, & Van Der Molen, 2016;Van Der Veen, Van Der Molen, Van Der Molen, & Franken, 2016), while later ERP processing stages (P300 component) reflected expected acceptance judgements (Van Der Veen, Van Der Molen, Sahibdin, & Franken, 2014; or general expectancy effects (Dekkers et al, 2015). In task versions that omitted the expectancy manipulation, early feedback evaluation was also reflecting acceptance vs. rejection judgements (Kujawa et al, 2014;Sun & Yu, 2014).…”
Section: Introductionmentioning
confidence: 98%